PENGARUH GAYA KEPEMIMPINAN TERHADAP KINERJA PEGAWAI MELALUI DISIPLIN DAN MOTIVASI KERJA PEGAWAI PPSU KELURAHAN DUREN SAWIT JAKARTA TIMUR - Wisnu Saputra; Imam Wibowo (Jurnal Manajemen Bisnis Krisnadwipayana, 2017)
This study aims to analyze the influence of leadership style on employee performance through discipline and work motivation. The sampling technique used is the census because the sample under study is the whole of the population. As many as 70 employees of PPSU Duren Sawit. The analytical tool used path analysis with the help of SPSS version 20. The results showed the variable discipline and motivation significantly cannot mediate the direct relationship of leadership style to employee performance, leadership style directly and insignificant influence on employee performance and leadership style directly influence And significant to discipline, leadership style has direct and significant influence to motivation, discipline has direct and insignificant effect on employee performance and motivation to directly and insignificantly affect employee performance.